New scenarios for orientation policies - Grimaldi, Anna; Ancora, Anna (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In light of the current challenges, highlighted by the most recent data showing high school drop-out rates, low tertiary education and low employability, especially among young people, it seems more necessary than ever to focus attention on possible new scenarios for guidance policies. The 2030 strategy proposes integrated interventions in the fields of education, employment, social inclusion and civic participation to meet the needs for inclusiveness and social growth. A survey on 3,642 young Italians aged between 15 and 29 reveals a low use of guidance services and a low awareness of the labour market, underlining the need to improve orientation policies. Future prospects suggest a holistic and continuous orientation approach, centred on ‘life-design’ and on the integrated construction of self and career path.